Activity Profiles by Position in Youth Elite Soccer Players in Official Matches - Pettersen, Svein Arne; Brenn, Tormod (Sports Medicine International Open, 2019)
In order to investigate activity profiles and external load patterns in elite youth soccer players, we studied high-intensity activity patterns, maximum running speed, and temporary and end-of-match decline in external load in 54 U17 players (96 match observations) over a full season of official match play.Wide midfielders covered most high-intensity running (HIR) distance (1044.2 m), most sprinting distance (224.4 m), and the highest number of accelerations (185.2); center defenders had the lowest values for these activities (508.3 m, 85.1 m, and 119.0), respectively. Wide midfielders had the highest and center defenders had the lowest maximum speed (30.3 km · h − 1 and 28.6 km · h − 1), respectively. During the matches, players in all playing positions displayed a significant drop in HIR distance, sprinting distance, and number of accelerations. This was especially pronounced in the 5 min following the 5-min peak period and in the last 5-min period for sprinting distance.There are substantial differences in activity profiles by positions, but all players show temporary and end-of-match drop in external load. The variation in activity profiles by playing position in this study may aid in the design of training programs. The considerable end-of-match drop in external load observed raises the question of the favorability of 90 min match times for U17 players.
Keywords: tracking; external load; playing position; high-intensity profile; maximum speed